Conceptions of disability among physiotherapists: an exploratory qualitative study - Dalboni, Gláucia L; Garcêz, Regiane L; Assis, Ítalo C; Vaz, Daniela V (Physiotherapy theory and practice, 2023)
Physiotherapists' (PTs) assumptions about disability, for the most part unrecognized and unquestioned, may or may not be aligned with the vision of the International Classification of Functioning, Disability, and Health (ICF). They can influence a wide range of PT practices and impact the lives of patients. To investigate whether PTs at different stages of their training rely on medical, social, or biopsychosocial conceptions of disability in line with the International Classification of Functioning, Disability and Health (ICF). A qualitative study with three focus groups: 1) PT students at the beginning; and 2) at the end of their training; and 3) PTs active in several different clinical fields. Content analysis was used identify definitions, causes, judgments, and solutions to disability. Some clinicians and senior students expressed views of functioning and disability as interactive, situational, continuous, and ubiquitous features of the human condition. However, in all groups there was a strong predominance of medical definitions and causal attributions for disability, some fitting the tripartite linear causal logic from impairment to subnormal performance to social disadvantage. Most of moral judgments were negative and associated disability with a 'diminished state,' personal loss, and suffering. Surprisingly, most solutions to disability-related problems were of a social or interactionist character, including vigilance against ableism. Results revealed paradoxical conceptions and point to challenges of ensuring a deeper understanding of non-medical framings, to avoid an uncritical adoption of the ICF that may neutralize its potential to challenge culturally entrenched medical conceptions of disability.